2015
DOI: 10.1186/s12879-015-1253-9
|View full text |Cite
|
Sign up to set email alerts
|

Health system delay in treatment of multidrug resistant tuberculosis patients in Bangladesh

Abstract: BackgroundBangladesh is one of the 27 high burden countries for multidrug resistant tuberculosis listed by the World Health Organization. Delay in multidrug resistant tuberculosis treatment may allow progression of the disease and affect the attempts to curb transmission of drug resistant tuberculosis. The main objective of this study was to investigate the health system delay in multidrug resistant tuberculosis treatment in Bangladesh and to explore the factors related to the delay.MethodsInformation related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
3
31
1
Order By: Relevance
“…Frontline HCW routinely failed to suspect and test for MDR-TB suggesting that educational initiatives directed at HCW may have considerable programmatic benefit. Yet diagnostic delay was common even in centers that provided TB services, contrary to other countries where patients who attended TB centers had an advantage of being suspected and screened early [12]. Likely more important is that the health system lacks efficient mechanisms for onsite specimen testing or referral of specimens and relaying of results, a common phenomenon occuring in many developing countries [13], but one in which if ameliorated would concurrently raise awareness and testing for MDR-TB among the HCW.…”
Section: Discussionmentioning
confidence: 99%
“…Frontline HCW routinely failed to suspect and test for MDR-TB suggesting that educational initiatives directed at HCW may have considerable programmatic benefit. Yet diagnostic delay was common even in centers that provided TB services, contrary to other countries where patients who attended TB centers had an advantage of being suspected and screened early [12]. Likely more important is that the health system lacks efficient mechanisms for onsite specimen testing or referral of specimens and relaying of results, a common phenomenon occuring in many developing countries [13], but one in which if ameliorated would concurrently raise awareness and testing for MDR-TB among the HCW.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Bangladesh National TB Control Programme (NTP) covers 99% of the population and provides free services including TB medications, significant delays in care-seeking, treatment initiation and completion for drug-sensitive and drug-resistant TB remain 2,3 , despite the roll out of rapid molecular diagnostics such as Xpert® MTB/RIF (Cepheid, Sunnyvale, CA) 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…26 Possible reasons for delays in starting treatment in Zimbabwe might be the time taken in conducting the baseline biochemistry tests on liver and renal function and the decision to start MDR-TB treatment, which is made by the clinical management team. Previous studies conducted elsewhere have shown that delayed treatment is due to a combination of patient and health system factors, [27][28][29] and these need to be addressed.…”
Section: Public Health Action Managing Rmp-resistant Tb In Zimbabwe 126mentioning
confidence: 99%